Bullet for a Ranger [large type] - Griffin, James J. (A Texas Ranger Jim C. Blawczyk novel, 2022)
"Jim Blawcyzk is in jail in the town of Quitaque, Texas, accused of murdering a saloon girl. Someone in the town wants Blawcyzk out of the way at all costs. With his trial fast approaching, and everyone in town convinced of his guilt, Jim must somehow find a way from his jail cell to prove his innocence, and fast. With his only ally the town padre, the task appears impossible even for the resourceful Blawcyzk. But Texas Ranger Jim Blawcyzk is no ordinary man. With the help of the padre, he escapes, killing the marshal in the process. Now he is a fugitive with a posse hot on his trail. Can he find a way to stay alive long enough to prove his innocence and complete the job he was sent to do in Quitaque?"--